ANALISIS TERHADAP PERATURAN KAPOLRI NOMOR 6 TAHUN 2010 TENTANG MANAJEMEN PENYIDIKAN OLEH PENYIDIK PEGAWAI NEGRI SIPIL - Penti Zahara; Syamsir Syamsir (Limbago: Journal of Constitutional Law, 2021)
Abstract In disclosing a case, Civil Servant Investigators with Indonesian National Police Investigators really need the principle of coordination, the Coordination Principle in laws and regulations can be in the nature of coordination, supervision, capacity building and providing instructions. Supervision is the process of observing the implementation of all activities of Civil Servant Investigators in the context of carrying out an investigation that is being carried out which can be justified materially or formally. The Coordination function between Civil Servant Investigators and Polri Investigators aims to unite and adjust activities, connect with each other, involve and adjust activities, regarding linkages so that these activities become a work unit, Civil Servant Investigators as part of The Criminal Justice system has a good and harmonious working relationship with the Indonesian National Police Investigators. Keywords: Coordination, Supervision, Investigator Abstrak Dalam mengungkao suatu perkara, Penyidik Pegawai Negeri Sipil dengan Penyidik Kepolisian Republik Indonesia sangat memerlukan asas koordinasi, Asas Koordinasi di dalam peraturan Perundang-undangan dapat bersifat Koordinatif, pengawasan, pembinaan kemampuan serta pemberian petunjuk. Pengawasan adalah proses pengamatan dari pelaksanaan seluruh kegiatan Penyidik Pegawai Negeri Sipil dalam rangka pelaksanaan penyidikan yang sedang dilakukan dapat dibenarkan secara material maupun formil. Fungsi Koordinasi antara Penyidik Pegawai Negeri Sipil dengan Penyidik Polri bertujuan untuk menyatukan dan menyesuaikan kegiatan-kegiatan, menghubungkan satu sama lain, menyangkut dan menyesuaikan kegiatan-kegiatan, menyangkut pautkan sehingga kegiatan-kegiatan tersebut menjadi suatu unit kerja, Penyidik Pegawai Negeri Sipil sebagai bagian dari sistem Peradilan Pidana mempunyai hubungan kerja yang baik dan harmonis dengan Penyidik Kepolisian Republik Indonesia. Kata Kunci : Koordinasi, Pengawasan, Penyidik